The influence of social support on students’ academic resilience through self-efficacy - Nasution, Muhammad Faisal Ramadhan; Dewi, Salamiah Sari; Fadilah, Risydah (Jurnal Psikologi Terapan dan Pendidikan, 2024)
Students who can maintain their abilities and function competently throughout their educational journey until completion are considered resilient. To become a resilient student, several attributes are necessary, both internal and external. Internally, self-efficacy the belief in one’s ability to complete tasks and fulfill obligations is crucial. Externally, social support from family, friends, and significant others plays a vital role. This study aims to examine the effect of social support on students’ academic resilience, with self-efficacy serving as a mediating variable. This study employs a quantitative methodology involving a sample of 270 students from a private university in Medan, with participants aged between 21 and 27 years. The instruments utilized in this research included the MSPSS scale, the General Self-Efficacy Scale, and the Academic Resilience Scale. Mediation analysis conducted using PLS-SEM4 showed that self-efficacy significantly mediates the relationship between social support and academic resilience, as indicated by a t-statistic of 4.440 (greater than 1.96) and a p-value of 0.000 (less than 0.05). This study's findings suggest that self-efficacy partially mediates the relationship between social support and academic resilience among students. Specifically, students who receive strong social support and possess high self-efficacy are more likely to confront their challenges and fulfill their academic responsibilities, ultimately developing resilient students.